(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Geodesy and Geographic Information Systems (GIS) are fields that have become widely used globally through modern discoveries and technologies. Geodesy is the science that studies the shape and dimensions of the Earth’s surface, with precise and accurate measurements being crucial in infrastructure and development projects. Geographic Information Systems, based on geodetic data, allow the storage, analysis, and visualization of geographic information. GIS technologies enable the expansion, management, and optimization of data. These systems are applied in various fields, including urban planning, ecology, transportation, and agriculture.